2016
DOI: 10.1007/s00404-016-4016-y
|View full text |Cite
|
Sign up to set email alerts
|

Do T1a breast cancers profit from adjuvant systemic therapy? A multicenter retrospective cohort study of 325 T1a-patients

Abstract: There is an association between AST and improved RFS or OAS for breast cancer patients with T1a tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…This is in line with the results previously described by the BRENDA study group and published by Wolters et al [10] . There, pT1a patients with infiltration of lymph nodes who received AST showed improved RFS and OAS due to AST.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is in line with the results previously described by the BRENDA study group and published by Wolters et al [10] . There, pT1a patients with infiltration of lymph nodes who received AST showed improved RFS and OAS due to AST.…”
Section: Discussionsupporting
confidence: 83%
“…We therefore avoid the term "statistically significant." Statistical analyses were carried out with SPSS (22) and NCSS (10).…”
Section: Statisticsmentioning
confidence: 99%
“…In Ignatov et al's study of 919 patients with T1a,b breast cancer, chemotherapy with trastuzumab was associated with a significant increase in 5‐year survival from 81% to 96% in patients with HER2 + tumors which constituted 20% of the study cohort . Similarly, Wolters et al demonstrated a significant survival benefit to chemotherapy for HER2 + T1a,b tumors. However, these two studies included patients with node‐positive disease.…”
Section: Discussionmentioning
confidence: 95%
“…The comprehensive BRENDA database with a large number of patients and a long follow up provided by a network of 17 certified breast cancer centers with information on treatment and survival, annual audits for the data quality has provided valuable data for healthcare research [6, 10, 11, 1316, 45]. The follow up was done according to the German breast cancer guidelines [1].…”
Section: Discussionmentioning
confidence: 99%